STRATEGI PORTOFOLIO KORPORAT: DIVERSIFIKASI VS. FOKUS UNTUK KEBERLANJUTAN USAHA PADA PERUSAHAAN MANUFAKTUR - Uning Heri Gagarin; Yeni Trisna Purba; Yohanis Rumbiak (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study examines corporate portfolio strategies in manufacturing firms by comparing two main approaches—focus strategy and diversification strategy—and assessing the role of sustainability through ESG-based diversification. The research aims to (1) compare the effectiveness of focus versus diversification, (2) analyze their impacts on financial performance and risk management, and (3) explore how sustainability-oriented diversification can generate competitive advantage and support long-term growth. The study applies a mixed-methods approach, combining quantitative analysis using key financial performance indicators (e.g., ROA, ROE, revenue growth, diversification index, and debt ratio) with qualitative case studies. The findings indicate that focus strategy generally delivers better market performance, with an average shareholder return (rTSR) of 2.3% compared to 1.6% for more diversified firms. Nevertheless, diversification remains important for spreading risk and sustaining growth stability. ESG-based diversification further strengthens innovation, mitigates regulatory and reputational risks, and enables access to new markets that increasingly demand environmentally friendly products. The study recommends an integrated approach: strengthen core competencies first, then pursue measured diversification into related segments while integrating ESG principles, enabling manufacturing companies to achieve business sustainability amid global uncertainty.